Obstetric shock and shock in obstetrics – steady obstetrical syndrome - Anis Cerovac; Dubravko Habek; Elmedina Cerovac; Jasna Čerkez Habek (Medicinski glasnik, 2022)
Obstetric shock (OS) has been defined as a life-threatening cardiovascular collapse syndrome associated with pregnancy, childbirth and puerperium (obstetrics causes), and is the most significant cause of high maternal mortality (MM) throughout human history. Shock in obstetrics (SIO) refers to indirect causes of non-obstetrics causes in pregnancy, childbirth and puerperium (polytrauma, aesthetic incidents, cardiovascular or cerebrovascular incidents, other septic syndromes). The goals of OS treatment are: to quickly detect the location or cause of bleeding / injury / inflammation, prevent the progression of shock, prevent massive transfusions, preserve the uterus (and adnexa), and preserve fertility if possible. Surgical treatment of septic shock includes exploratory laparotomy (laparoscopy), ectomy or resection of the necrotized organ, abdominal lavage with multiple drainages, continuous peritoneal drainage with lavation, extensive triple antibiosis per admission or per antibiogram and thromboprophylaxis. OS seems to remain a permanent miasma in practical clinical obstetrics, which we will not be able to influence, because we have obviously caused today's increase in MM from haemorrhagic OS by iatrogenic increase in the number of caesarean sections, especially elective ones.
Keywords: Caesarean section; circulatory collapse; maternal mortality; pregnancy